2005
DOI: 10.1080/10428190500046778
|View full text |Cite
|
Sign up to set email alerts
|

Severe bone marrow aplasia following imatinib mesylate in a patient with chronic myelogenous leukemia

Abstract: Imatinib mesylate, a signal transduction inhibitor molecule, has been introduced in the treatment of chronic myelogenous leukemia (CML) since May 2001. By its unique mechanism of action, the drug has revolutionized the management of chronic phase CML. The drug is generally well tolerated. A number of hematological and non-hematological side-effects have been reported. Fatal bone marrow (BM) aplasia has rarely been reported. A 46-year-old women with chronic phase CML was treated with imatinib. Six weeks later s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Marrow hypoplasia following imatinib therapy has infrequently been reported [7][8][9].Bone marrow hypoplasia is a potentially fatal adverse side-effect of imatinib and can present in any phase of CML. In one of the studies [9], there were five patients with severe hypoplasia (bone marrow cellularity between 5 and 10%) the Bcr/Abl was positive in all patients at the time of hypoplasia.…”
Section: Discussionmentioning
confidence: 98%
“…Marrow hypoplasia following imatinib therapy has infrequently been reported [7][8][9].Bone marrow hypoplasia is a potentially fatal adverse side-effect of imatinib and can present in any phase of CML. In one of the studies [9], there were five patients with severe hypoplasia (bone marrow cellularity between 5 and 10%) the Bcr/Abl was positive in all patients at the time of hypoplasia.…”
Section: Discussionmentioning
confidence: 98%
“…To the best of our knowledge, only three case reports of bone marrow aplasia has been reported in the literature till date. Lokeshwar et al reported a case of severe bone marrow aplasia following 6 weeks of imatinib mesylate therapy and the patient died of pulmonary mucormycosis [7]. Chng and Tan also reported a case in which bone marrow aplasia occurred after prolonged period of imatinib therapy [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although IM has not been reported so far as a causative agent for GMT, changes in BM architecture have been associated with this treatment. These consisted mainly of a rapid decline in cellularity with various degrees of fibrosis, severe aplasia and even BM necrosis [14,15,16,17,18,19]. Several hypotheses might explain the association between IM treatment and BM stromal processes.…”
Section: Discussionmentioning
confidence: 99%